Sistem Informasi Manajemen Internet Dan Ekstranet - Ruth Haryanti; Vip Paramarta; Maharanny Wulansari; Aulia Dini Rachmadanti; Febri Diotama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This rapid development of technological knowledge can help humans fulfill the new order of civilization in the era of technology that was created to make daily work easier. Computers are not only used as electronic typewriters but have been used to increase work and business productivity. An information system is a system that provides information for the decision-making process at every level in an organization. Network users control what they do through graphical applications prepared for the user. All data including electronic mail (e-mail), databases are stored on the server. Special servers for the internet or even for certain internet functions are the heart of information on the internet. Getting many benefits from the internet, for example reducing communication costs, improving communication and coordination skills, distributing knowledge and providing facilities for e-business or e-commerce, including reducing communication costs. In this article the author explains the implementation of the internetworking concept (internet and extranet), the benefits of using each and the development that can be carried out from the internetworking concept, components and forms of application of the internetworking.